A short history of ethics : a history of moral philosophy from the Homeric Age to the twentieth century - MacIntyre, Alasdair C. (University of Notre Dame Press, 1998)
"In this classic work, Alasdair MacIntyre guides the reader through the history of moral philosophy from the Greeks to contemporary times. He emphasizes the importance of a historical context to moral concepts and ideas. MacIntyre illustrates the relevance of philosophical queries on moral concepts enabling the reader to understand the importance of a historical account of ethics."--Jacket.